THE EFFECTIVENESS OF USING FIRING LINE STRATEGY TO TEACH READING COMPREHENSION - Assegaf, Husein; Ikhsanudin, Ikhsanudin; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to find out whether the firing line strategy is effective to teach reading comprehension. The researcher conducts a pre-experimental study entitled â€œThe Effectiveness of Using Firing Line Strategy to Teach Reading Comprehensionâ€. The participicants of this research were the eight grade students of SMP Islam Tazkiyah Pontianak. In the research, the researcher use a pre-experimental study (one group pre-test post-test design). The data in this research were gathered by using measurement technique and statistical analysis. As a result, there were differences in the average post-test results. It was proven by the results of TTable TArithmatic = 2,042 and 9,406 (9,406 > 2,042). It was found out that the reading comprehension of students after using firing line strategy was higher than before using it, and the effect size proved the results by 1,59. In conclusion, the firing line strategy is effective to teach reading comprehension to the eight grade students of SMP Islam Tazkiyah Pontianak.Â Â Keywords: Firing Line Strategy, Pre-Exprimental Study, Reading Comprehension Â